OPINION ESSAYS IN PROMOTING NURSING STUDENTS' WRITING ACHIEVEMENT - Arief Pamuji (Universitas Tridinanti Palembang, 2022)
In writing English essay, the students often face the problem. One of the causes as there was no appropriate method to be used to explore their ideas or paradigm. The opinion essay was one of the good ways to be used in overcoming the problem. The objective of this research was to see the differences in students’ writing achievement on nursing students between those who were taught using opinion essay and those who were not. A quasi-experimental method was used, with a non-equivalent group design for the pre-test and posttest. The samples consisted of 50 fifth-semester students of conversion nursing students from STIK Bina Husada. An essay writing test was utilized to collect data. The data were obtained by using pre and post writing test. The score of writing in control group in post test was 70 and in experiment group with the highest score was 92.The mean difference of post-test from both groups was 12.88, standard error difference was 1.68, and t-obtained was 7.46 at a significant level of p<0.05. From the result it can be concluded that the use of opinion essays leads the students to explore more ideas, point of view and paradigm into English written essays and this method can be used by lecturer to enhance the student’ writing achievement of STIK Bina Husada PalembangKeywords:opinion essay, writing achievement